DEFENSE MECHANISM IN SARAH J. HARRIS’ THE COLOUR OF BEE LARKHAM’S MURDER - Eko Susanto; Ambar Andayani (TANDA, 2021)
This research focuses on how a person with mental illness uses defense mechanism which the condition is perfectly seen in Jasper Wishart in the novel The Colour of Bee Larkham’s Murder by Sarah J. Harris. This study aims to find and explain about mental illness that affects the main character’s life and defense mechanism that the character uses. The methods used in this research are library research and psychological approach that are applied to analyse psychological problems of the main character. The result shows that mental issues make Jasper have difficulties throughout his life. Autism and synaesthesia conditions have made him incapable to communicate and to recognize people. He has two ways of defense mechanism: repression and regression, repression by forcefully forgetting his problems, regression by reversing psychological movement.